2015
DOI: 10.1017/s002237781500077x
|View full text |Cite
|
Sign up to set email alerts
|

Ion-acoustic shocks with reflected ions: modelling and particle-in-cell simulations

Abstract: Non-relativistic collisionless shock waves are widespread in space and astrophysical plasmas and are known as efficient particle accelerators. However, our understanding of collisionless shocks, including their structure and the mechanisms whereby they accelerate particles remains incomplete. We present here the results of numerical modeling of an ion-acoustic collisionless shock based on one-dimensional (1D) kinetic approximation both for electrons and ions with a real mass ratio. Special emphasis is made on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…We further highlight the following findings of this paper: Based on the numerous PIC simulations, available in the literature (e.g., [9,10,41]), we may speculate that when the Mach number exceeds its critical value M 2 , obtained in this paper, the shock evolution becomes time dependent; ions reflect intermittently. One example of such dynamics, Fig.5, we adopted from the recent PIC simulations [41] (see also Appendix for a further brief discussion of this result). For yet higher Mach numbers, the upstream and downstream flows do not couple together, but rather penetrate through each other, not being perturbed significantly.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We further highlight the following findings of this paper: Based on the numerous PIC simulations, available in the literature (e.g., [9,10,41]), we may speculate that when the Mach number exceeds its critical value M 2 , obtained in this paper, the shock evolution becomes time dependent; ions reflect intermittently. One example of such dynamics, Fig.5, we adopted from the recent PIC simulations [41] (see also Appendix for a further brief discussion of this result). For yet higher Mach numbers, the upstream and downstream flows do not couple together, but rather penetrate through each other, not being perturbed significantly.…”
Section: Discussionsupporting
confidence: 67%
“…As the beam "hydrodynamics" is truly collisionless, their intersection will result in a multi-flow state of the reflected beam. Such states copiously emerge in simulations, e.g., [10,41,42], along with…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is more important than possible shock rippling effects, not captured by 1D simulations. Besides that, shock rippling and its impact on particle reflection cannot be accurately characterized within hybrid simulations and require a full kinetic treatment (Liseykina et al 2015;Malkov et al 2016;Malkov 2017). For the reasons explained in detail in sections 4.2 and 4.3 we deliberately choose the 1D treatment as a first step in a systematic study of the A/Z dependence of injection efficiency.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…Onedimensional PIC simulations [12] have examined the interaction of a hot pair cloud that expands into an ambient plasma. The simulations have shown that electron phase space holes [13][14][15][16], which form and evolve on electron time scales, and the ion acoustic solitary waves that are tied to them [17] could be an efficient means to accelerate ions to high energies especially when the ion acoustic solitary waves break [18]. Our aim is to study these processes in more detail with a two-dimensional particlein-cell (PIC) simulation that resolves competing multidimensional instabilities such as those that destroy phase space holes in more than one dimension [13].…”
Section: Introductionmentioning
confidence: 99%